Local knowledge of the community in Cintaratu Village, Pangandaran, Indonesia on traditional landscapes for sustainable land management - Ruhyat Partasasmita; NADYA TIMURIA CAHYANI; JOHAN ISKANDAR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Partasasmita R, Cahyani NT, Iskandar J. 2020. Local knowledge of the community in Cintaratu Village, Pangandaran, Indonesia on traditional landscapes for sustainable land management. Biodiversitas 21: 3606-3616.  Cintaratu, a village in Parigi Sub-district, Pangandaran District, West Java province, Indonesia has various landscapes. The recent developments of the community reflect a shift in values towards the attainment of economic prosperity. However, scaling-up the use of landscapes in this capacity can cause negative impacts. A cultural approach to landscape management can assist the village community in identifying sustainable practices. The purpose of this study was to elucidate the community's knowledge of the variety of traditional landscapes that exist in Cintaratu Village and the historical influence on variations in the landscapes. The qualitative method was applied in this study. The result of the study showed that some landscapes, i.e., leuweung karamat (sacred forest), kebon (garden), sawah (rice field), astana (grave/ tomb), pamukiman (residential area), pekarangan (homegarden), walungan (river), solokan (small river), tampian (bathing and washing place for residents), and balong (fish pond) are documented in Cintaratu Village. On the basis of ecological history, it has been revealed that village community’s behaviors have changed various landscapes in Cintaratu Village. Conservation efforts carried out by the people themselves towards the traditional landscapes are usually associated with a customary prohibition or pamali that develops in the village community. The local people of Cintaratu recognize various landscapes that can be classified as natural and cultural landscapes. Based on the information provided by informants, the village landscape changes can be traced from the 1780s to 2019. The history of these landscape changes is the result of various factors, including an increase in population density, the implementation of government policies, and market economic development in the village.